PERTAMBAHAN ALAMI (NATURAL INCREASE) TERNAK SAPI BALI DI KECAMATAN WAESAMA KABUPATEN BURU SELATAN - Drasela Duila; Demianus F. Souhoka; Jusak Labetubun (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2021)
The objective oictf this research was to explore natural increase rate of Bali cattle in Waesama district of South Buru Regency. The research applied survey method. The observe variables respondent characteristics, and cattle population structure, reproduction potency,ownership, mortality rate, and its natural increase rate. The results showed that number of population. Hasil penelitian menunjukkan bahwa in Waesama District there are 221 cattles with birth rate 20.73 percent, mortality rate 2.18 percent and natural increase rate 19,00 percent.